Study of literary works in the aspect of artistic time and space continuum (on the example of literature lessons) - Gulnaz Nurfatovna Mukharlyamova; Dilaria Maratovna Abdullina (Вестник Майкопского государственного технологического университета)
The relevance of the article is due to the lack of attention to the issues of studying literary works through the prism of the concepts of artistic time and space in Literature lessons at school. The use of the categories of artistic time and space in the analysis of a work allows us to expand theoretical and literary knowledge of students, improve the perception of a literary text, and form an adequate emotional and value attitude to it. Their consideration is carried out in conjunction with plot, compositional and genre features of a literary work. The article outlines the problem of the need to disclose the main ways of studying a literary work on the basis of the analysis of a chronotope. The purpose of the study is to consider the features of studying a literary work in the aspect of artistic time and space in the lessons of native (Tatar) Literature in a secondary school. The research methods used are theoretical analysis, synthesis, generalization of information. The results. The study of a literary work in the aspect of artistic time and space is based on the phased development of the categories of chronotope; analysis of specific chronotopic images; use of binary oppositions in the analysis of literary text; students' understanding of the existence of different types of spatio-temporal relationships.